O uso de estratégias metacognitivas na resolução de problemas matemáticos envolvendo números racionais por alunos do 8º ano do ensino fundamental de uma escola pública de Sinop/MT - Costa, Luciane Reichert (2018)
The present research aims to investigate if the use of metacognitive strategies potentiates the resolution of mathematical problems of students of the 8th year of the third cycle of Elementary School. For this, we base the theoretical contribution of Mizukami (1986), Moreira (1999), Freire (2005) and Lorenzato (2006) to understand the teaching-learning process and its methodological approaches, as well as the diagnostic evaluation of this process according to Darsie (1996), Luckesi (2002), Delgado (2011), Blasis, Falsarella and Alavarse (2013), Viana (2013) among others. In the comprehension of solving mathematical problems we are based on Glaeser (1973), Dante (1991 and 1998), Pozo and Echererria (1998), Lester (2001), Câmara dos Santos (2002), Araújo (2009) among others. We also draw on Antonijevic and Chadwick (1982), Koutselini (1991), Baird (1991), Costa (1994), Darsie (1998), Flavell (1999), Carrasco (2000), Portilho (2001), Ribeiro ), Araújo (2009), Dreher (2009), Leite (2011), Speráfico (2013) among others, to understand the concept of metacognition and metacognitive strategies. Based on the theoretical contribution and the question: "The development of metacognition with the use of metacognitive strategies enhances students' learning in solving mathematical problems?", We developed an action research with seven (07) eighth Elementary School of the Paulo Freire State School in Sinop / MT, and a sample of the students that were evaluated with performance "below the baseline" in the Diagnostic Assessment of State Public Education of Mato Grosso (ADEPE-MT) in 2016. For the production of data , we analyzed the results of external evaluations carried out by the students of the study and verified that the descriptor: "Recognizing different representations of a rational number", according to the ADEPE / MT Reference Matrix presented the lowest performance, in this sense, we conduct semi-structured interviews, the pre-test based on external evaluation questions that refer to the different representations is a rational number, and the result of the pre-test proved the result of the external evaluation. Then, we planned the intervention with the use of metacognitive strategies in problem solving, focusing the rational numbers and we performed the intervention, which was developed during seven (07) meetings in which the students subject of the research, solved problems based on the different representations of the rational numbers with the use of metacognitive strategies and still socialized the procedures and strategies used to solve the problems proposed. Finally, we still applied the post-test, in which the students of the research presented a significant improvement in performance in relation to the pre-test. The data produced during the intervention and the results of the pre- and post-test, lead us to assume that the use of metacognitive strategies in solving mathematical problems enhances learning, since students demonstrate: knowledge by focusing on understanding the proposed problem; planning when choosing the best procedures and strategies for the resolution of the same; and control over the entire problem solving process proposed.